ABU BAKAR ASH-SHIDDIQ'S EDUCATIONAL LEADERSHIP MODEL - Sidiq, Heri Purwanto; Indra, Hasbi (Department of Islamic Education Management, 2023)
The purpose of this research is to find out the educational leadership model of Abu Bakar Ash-Shiddiq. The method used in this study is the literary method using primary data that is directly related to the figure of Abu Bakar Ash-Shidiq, especially the book 'Abqariyah Ash-Shiddiq written by Abbas Mahmud 'Aqqad supported by secondary data related to leadership theories. The results of the study found that the characters of Abu Bakar Ash-Shiddiq include loyalty to leaders, having a wise attitude, being fair, having determination and strength, having determination and azzam, supervising and caring, and having a sense of humanity and compassion. While the application in education related to the character of Abu Bakar Ash-Shiddiq can be described in terms of being fair in educating, wise in educating, loyal to leaders in educational institutions, having compassion in educating, supervising and caring in educating, having determination in educating, and having strong determination in education. The conclusion of this study is that the character of Abu Bakar Ash-Shiddiq is the character of a successful leader in fostering and educating his people.